The firewalkers - Castillo, Erwin E. (Diliman, Quezon City The University of the Philippines Press, 2003)
Set in 1913, The Firewalkers follows police sergeant Gabriel Diego in the hard-bitten mountain town of Lakambaga, Cavite. Silver-spurred Americans and their new rule of law bristle against the fading glory of Gabriel Diego’s blood uncles, old generals spurned by Emilio Aguinaldo during the Philippine-American War. Meanwhile, a monster leaves behind mangled corpses of children as the cowboy Apache Kid searches the town for the remote memories of something else more magical.
With: The Firewalkers : going farther back than Joaquin / Cesar Ruiz Aquino.
Keywords: Philippine fiction (English)